Krisis Budaya Tradisional: Generasi Muda dan Kesadaran Masyarakat di Era Globalisasi - Indriani, Egita Dwisari; Dewi, Dinie Anggraeni; Hayat, Rizky Saeful (Indo-MathEdu Intellectuals Journal, 2024)
The presence of globalization plays a role in the development or change of social interactions, cultures, or habits of Indonesian people, especially the younger generation who tend to learn foreign cultures rather than their own. Awareness of traditional culture is essential to ensure that traditional culture still exists. The research method used is a literature study with data collection techniques through scientific articles, books, and relevant references. The result of this study is the need for public awareness of the importance of preserving traditional culture, as well as the younger generation has an important role in preserving traditional culture, namely being able to increase cultural competence, participate in cultural activities, maintain politeness in association, and the reintroduction of local culture through education, especially for elementary school children